Contributions of integrated aflatoxin management strategies to achieve the sustainable development goals in various African countries - Ortega Beltran, A.; Bandyopadhyay, R. (Elsevier, 2021)
In 2015, all United Nations Member States adopted the 2030 Agenda for Sustainable Development to achieve peace and prosperity for all people in the planet. Meeting that ambitious agenda depends on fulfilling all objectives of 17 Sustainable Development Goals (SDGs). Multiple approaches by diverse actors, many of them interconnected, will allow achieving each SDG. However, with compromised food security and food safety, many SDGs will not be realized. In sub-Saharan Africa (SSA), maize and groundnut are two staple crops frequently contaminated with aflatoxins, which threaten food security and food safety. Aflatoxins are extremely dangerous compounds produced primarily by the fungus Aspergillus flavus. Even at minute concentrations, aflatoxins negatively influence health, income, and trade sectors. Farmers, traders, industries, and consumers become affected. However, practical solutions exist. Non-aflatoxin producing isolates (referred to as atoxigenic) of A. flavus can decrease crop aflatoxin content when used in biocontrol formulations to competitively displace aflatoxin producers during crop development. Typically, treated crops contain 80%–100% less aflatoxin than non-treated crops. The technology was developed by USDA-ARS for use in the US and has been adapted and improved for use in SSA where several products under the tradename Aflasafe are available. There are biocontrol products registered for use in 10 SSA countries and more are being developed. On the other hand, although highly effective, biocontrol is not a panacea. Less aflatoxin occurs across value chains when biocontrol is combined with other practices. In this review, we discuss how i) aflatoxin biocontrol products are developed, manufactured, licensed, and commercialized, ii) aflatoxin management strategies are designed, and iii) integrated aflatoxin management is or will soon be contributing to achieve, in several countries, many targets of most SDGs. We present integrated aflatoxin management as a model intervention contributing to tackle several challenges impeding prosperity and peace in SSA.